Preferences, perceptions and barriers to E-learning among medical students during COVID-19 pandemic lockdown in India - Suryawanshi, Deodatt M.; Venugopal, Raghuram (International Journal Of Community Medicine And Public Health, 2020)
Background: Following the imposition of the nationwide lockdown on 24th March 2020, many medical institutions adopted E-learning as a method to ensure continuity in medical education. Understanding perceptions and preferences of medical students and addressing their barriers are essential for a seamless learning experience. Methods: Data was collected using a semi-structured online questionnaire after obtaining informed consent. A total of 296 students of the second year MBBS and pre-final year were recruited using non probability sampling. Data pertaining to 286 students who returned the questionnaire was entered in Microsoft excel and analysed using SPSS version 21. Results: Majority of the participants 179 (62.5%) were female. Only 18 (6.2%) had advanced computer and internet usage skills. 138 (48.2%) students showed preference for blended mode of teaching. 203 (71.0%) of students showed preferences for non-interactive learning methods like slide share and YouTube videos. 180 (62.9%) cited that lack of personal interaction with the teacher followed by access to internet 67 (23.4%) and lack of hardware 53 (18.5%) as barriers in the e-learning. Significant differences were observed between female and male students in the teaching methods with regards to ease of understanding (p=0.009) and use of non-interactive platforms for e leaning (p=0.03). Conclusions: The study identified blended learning as an acceptable method of learning medical curriculum. Schedule flexibility, ease of understanding and absence of monotony of classroom teaching made e-learning more acceptable. lack of teacher-student interaction, lack of accesses to high speed internet and hardware were barriers perceived to e-learning among medical students.